1996
DOI: 10.1002/bies.950180110
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Sgs genes: Stage and tissue specificity of hormone responsiveness

Abstract: The up-and down-regulation of the salivary gland secretion protein (Sgs) genes during the third larval instar of Drosophila melanogaster are controlled by fluctuations of the titre of the steroid hormone 20-hydroxyecdysone (20E). Induction of these genes by a low hormone titre is a secondary response to 20E mediated by products of 20E-induced 'early' genes. Surprisingly, in the case of the Sgs-4 gene this response also requires a direct contribution of the 20Ereceptor complex. A model is presented which propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 68 publications
0
52
0
1
Order By: Relevance
“…At the mid-third instar larval stage (mid-L3), salivary glands begin producing highly glycosylated glue proteins (cargo) that traffic through the endoplasmic reticulum and Golgi before being incorporated into regulated secretory granules (glue granules) at the TGN (Jamieson and Palade, 1967a; Jamieson , 1967b;Beckendorf and Kafatos, 1976;Korge, 1977;Thomopoulos and Kastritis, 1979;Lehmann, 1996;Burgess et al, 2011). Indeed, we previously showed that clathrin and AP-1, which colocalize with the adaptor EpsinR (Liquid facets-relatedFlyBase) at the TGN, are essential for glue granule formation (Burgess et al, 2011).…”
Section: Phosphatidylinositolmentioning
confidence: 99%
“…At the mid-third instar larval stage (mid-L3), salivary glands begin producing highly glycosylated glue proteins (cargo) that traffic through the endoplasmic reticulum and Golgi before being incorporated into regulated secretory granules (glue granules) at the TGN (Jamieson and Palade, 1967a; Jamieson , 1967b;Beckendorf and Kafatos, 1976;Korge, 1977;Thomopoulos and Kastritis, 1979;Lehmann, 1996;Burgess et al, 2011). Indeed, we previously showed that clathrin and AP-1, which colocalize with the adaptor EpsinR (Liquid facets-relatedFlyBase) at the TGN, are essential for glue granule formation (Burgess et al, 2011).…”
Section: Phosphatidylinositolmentioning
confidence: 99%
“…3B), a time when larval ERR gene expression begins (Sullivan and Thummel, 2003), together with a global switch in gene expression that prepares the animal for entry into metamorphosis 1 day later (Andres et al, 1993;Cherbas et al, 2003). This so-called mid-third instar transition includes upregulation of EcR, providing sufficient receptor to transduce the high titer late larval 20E hormone pulse (Talbot et al, 1993), upregulation of the Broad-Complex, which is required for entry into metamorphosis (Kiss et al, 1988), and induction of the genes that encode a polypeptide glue used to immobilize the puparium for metamorphosis (Lehmann, 1996). The signal and receptor that mediate this global reprogramming of gene expression remain undefined.…”
Section: New Insights Into the Regulation Of Drosophila Xenobiotic Rementioning
confidence: 99%
“…Additionally, in Drosophila GFAT activity is stimulated for the synthesis of highly glycosylated salivary-gland glue proteins in late thirdinstar larvae [6]. The induction of glue-protein synthesis is a response to low-titre pulses of 20-hydroxyecdysone in salivary glands, while its termination is correlated with the high-titre pulse of 20-hydroxyecdysone at the end of the third larval instar stage [7]. In Drosophila irilis it has been demonstrated that the Abbreviations used : 8-Br-cAMP, 8-bromo-cAMP ; GFAT, glutamine : fructose-6-phosphate aminotransferase ; hGFAT, human GFAT ; Dmel/GFAT, Drosophila melanogaster GFAT ; PKA, protein kinase A ; UDPNG, UDP-N-acetylglucosamine ; GST, glutathione S-transferase ; DIG, digoxigenin ; AP, activator protein ; TBP, TATA-box-binding protein.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the mechanisms involved a knowledge of the molecular biology of the considered genes is necessary. The Sgs genes of D. melanogaster have been cloned and the regulation of their expression has been characterized extensively (for a review see [7]). Since molecular information on the Drosophila GFAT enzyme (Dmel\GFAT) and the structure and expression of its gene was unavailable we started a project for the characterization and molecular analysis of GFAT expression in D. melanogaster.…”
Section: Introductionmentioning
confidence: 99%